A Project Report On Risk Aware Mitogation For Manet Routing Attacks JEEVAN KUMAR R, NAVEEN KUMAR K, SURENDHAR J and DEEPAK RAI (2013)
INTERNAL GUIDE : Santhiya M EXTERNAL GUIDE: Sreedevi N USN NO : 1MJ10CS438, 1MJ10CS430, 1MJ08CS096 AND 1MJ08CS018 CARRIED OUT AT : Mvj College Of Engineering Bangalore-560067 ACC NO : PR1919
Keywords: Risk Aware Mitogation